Relationship between job stress, work engagement, job satisfaction, organization commitment and employees’ turnover intention in retail and consumer product industry in Melaka / Nur Farhana Hamidun - Hamidun, Nur Farhana (Faculty of Business and Management, 2019)
Employees’ turnover gives negative impact to Human Resource Managers in all organization. This caused Human Resource Manager needs to consider the cost for hiring the new employees in order to replace the previous employees. To avoid the unwanted issues regarding the employees’ turnover, HR manager need to know and investigate the factors that influencing the employees to leave the organization before find the solution how to retain the employees in the organization itself. Therefore, in this study, the researcher decides to investigate the relationship between job stress, work engagement, job satisfaction and organization commitment towards employees’ turnover intention in retail and consumer products in Melaka. The researcher had examined four factor which included job stress, work engagement, job satisfaction and organization commitment as independent variables. In order to obtain the result, the researcher used SPSS Based on the finding that the researcher obtained, the most significant factor is job stress.